(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2023)
The purpose of this study is to determine the level of satisfaction of consumers of educational services and determine if there is a correlation with sociodemographic variables, and based on this, seek strategies for students to increase their level of satisfaction with their career. The research was of a quantitative approach of descriptive and correlational scope, of cross-sectional design. The sample was made up of 224 participants belonging to 7 educational programs. The survey was used as a technique and the instrument for data collection is composed of eight items where an ordinal scale from 1 to 5 was used, where 1 is very little and 5 is very high, in addition to sociodemographic variables and the AMAI scale. to evaluate the NSE with 6 questions. The reliability of the instrument was verified through Cronbach’s alpha using the SPSS version 25.0 program, resulting in an acceptable value of 0.768. It was concluded that students have great satisfaction towards the prestige of the school and their peers, contrary to the schedules offered by the institution because they are less satisfied in this variable. Likewise, satisfaction has no correlation with the sociodemographic variables, except with the career they are studying and the desire of the parents to have studied a professional career.